Approaching the Subject of Violence: A Response-Based Approach to Working With Men Who Have Abused Others. (September 2014) - Todd, Nick; Weaver-Dunlop, Gillian; Ogden, Cindy
Traditional effects-based approaches to therapeutic work with men who have abused others often attempt to intervene by correcting personal deficits assumed to be causing the violence. This not only creates a hierarchical counseling relationship but also can inadvertently excuse aggressive actions. In this article, we outline a response-based alternative that emphasizes questions of choice, agency, and volition within a collaborative therapeutic relationship. Rather than impose external correction, we pay attention to details of how men describe their violent acts and position themselves as agents of those acts as we work toward supporting them in their own acts of self-correction.